A Study on the Impact of the Digital Divide in Digital Government Construction on the Equalization of Public Services (Journal of economic and management development research, 2025)
This paper aims to explore the complex impact of the digital divide on the equalization of public services during the process of digital government construction. The research points out that the digital divide has evolved from a single "access divide" to a multi-dimensional social stratification phenomenon covering access, skills, and outcomes. Against the backdrop of the increasing digitalization of public services, this divide systematically excludes digital disadvantaged groups such as the elderly, low-income individuals, and rural residents, not only hindering their effective access to basic services like healthcare, education, and social security but also potentially solidifying and exacerbating existing social inequalities. The article argues that the concept of digital inclusion must be placed at the core, and a comprehensive strategy including the construction of integrated online and offline service channels, the enhancement of digital literacy for all, and the improvement of top-level design should be adopted for governance, in order to ensure that the construction of digital government truly serves the goal of universal and fair access.
Keywords: Digital Government; Digital Divide; Public Services